INTERNAL CONTROL SYSTEM AND FINANCIAL REPORTING QUALITY OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Olorunfemi Gbenga Samuel (Malete Journal of Accounting and Finance)
Poor reporting quality is a destructive issue in the business world while the internal control is perceived as a form of assurance technique to the management and stakeholder. In response to series of abysmal financial reporting from Nigeria’s oil and gas sector, this study appraised the effect of internal control system on financial reporting qualities of the listed oil and gas sectors in Nigeria. A survey research design was employed and primary data were obtained through structured questionnaire distributed to 233 management staff, selected randomly from nine oil and gas firms in Nigeria. The data was subjected to multiple regression analysis and the study revealed that control activities, monitoring activities, control environment, and risk assessment have p-value of 0.000 and beta of 0.33; 0.56; 0.359; -0.323 respectively on the comparability of financial reports in Nigeria’s oil and gas sector. The study concludes that efficient internal controls system enhanced improved financial reporting quality. It was recommended that the management should implement efficient risk assessment system in place to ensure preventions from irregularities and compliance to standards and other regulatory requirements. Also, there should be an effective risk assessment to reduce mismanagement of firm’s assets.